(untitled) (Global Media Journal - German Edition, 2024)
Since 2014, Ukraine has started its public diplomacy (PD) activities to counter Russian aggression, intensifying these efforts in 2022 following the full-scale invasion. Despite this, much of Ukraine’s PD remains understudied, with existing research either outdated or primarily focused on specific aspects. This study aims to provide a comprehensive analysis of how Ukrainian public diplomacy is developed and implemented within a war-related context by comparing official PD strategy documents with the practices of state PD actors, particularly those targeting Germany. Using a case study method, this research incorporates document analysis and interviews with Ukrainian diplomats and PD practitioners. The findings illustrate how the key actors of Ukrainian public diplomacy operate, highlighting their goals, target audiences, narratives, and the challenges they face. The study reveals the contextual nuances of public diplomacy efforts in Germany. While core PD goals remain unchanged, practitioners have shifted focus, adapting narratives and refining their target audiences to address war-related issues. In line with increased international attention on Ukraine, communication efforts have been intensified to bridge gaps in global understanding of the war and to combat foreign public attention fatigue.